Comparison of spiral versus block curriculum styles in preparing medical students to diagnose and manage concussions. Issue 11 (25th May 2017) - Wright, Alexander D; Fraser, Sarah K; Smirl, Jonathan D; Donkelaar, Paul van
Abstract : Objective: Examine differences between the recently implemented integrated spiral (year 1) and conventional block (years 2-4) MD curriculum at University of British Columbia (UBC) with respect to knowledge of concussion diagnosis and management. Design: Cross-sectional survey Setting: UBC undergraduate MD program Participants: An online survey was distributed to all 1152 students currently enrolled in UBC medical school. To date, 123 surveys have been returned (10.7% response rate) with 58 first year students (integrated spiral curriculum) and 65 students in years 2-4 (conventional block curriculum). Females made up 60% of responses. Interventions: Online survey, hosted by FluidSurveys (Fluidware, Ottawa, ON), distributed through email. Outcome measures: Questions focused on demographic data, knowledge of concussion definitions, and management considerations. Main results: Majority of responses revealed both curriculums have promoted a strong understanding of concussion definition and related symptoms (84% correct response rate). Only 8.1% of participants believed that functional imaging (MRI or CT) is a mandatory assessment tool for concussions. Differences between the conventional and integrated curriculums included: understanding concussions can occur without direct impact to the head (91.4% integrated vs. 69.2% conventional: χ2(1)=43.325, p<0.001) and identifying long-term consequences of repetitive concussive injuries (dementia: 91.4% integrated vs. 66.2% conventional; death or severe disability with second impact syndrome: 77.6% integrated vs. 55.4% conventional). Conclusions: The findings from this study reveal a number of positive signs regarding the evolution of medical education in terms of concussion diagnosis and management. The integrated curriculum is taking further steps in advancing concussion knowledge in medical education. Competing interests: None.